The Cornwall Beaver Project: navigating the social-ecological complexity of rewilding as a nature-based solution - Jones, Mike; Jones, Chris (Frontiers in Conservation Science, 2023)
The story of the Cornwall Beaver Project is presented as the foundation of a review of the literature to consider the effects of beavers on geomorphological and hydrological processes, habitats, biodiversity, and people in agricultural landscapes in the UK. The review includes a comparison of the principles for rewilding as an approach to ecological restoration with IUCNs principles for Nature-based Solutions together with a summary of beaver reintroduction in Europe, and the impacts of beavers on hydrological and geomorphological processes, biodiversity and the human-wildlife conflict that arises from reintroduction. We note that rewilding principles require a paradigm shift in the relationship between humans and the rest of nature and a corresponding application of systems thinking to research, practice and policy. The combination of experiential and formal knowledge is assessed using a social-ecological systems framework to consider the potential of beavers to mitigate climate change impacts on agricultural landscapes in the UK and how rewilders might navigate the social complexity of beaver reintroduction to achieve large scale system transformation. We discuss the different lines of evidence about the impacts of beavers on landscapes as viewed through a system lens and conclude that: (1) beaver dams have considerable potential to store water but their ability to reduce flood risk is difficult to assess because of the complex interactions between the material available for dam construction, geomorphology, and the duration, extent and intensity of rainfall events; (2) beaver dams, especially when combined with buffer zones along water courses have considerable potential to enhance the resilience of agricultural landscapes and support a shift from intensive to agroecological farming; (3) scaling beaver reintroduction will evolve with the application of policies and practices that enhance the ability of land users to adapt and learn how to coexist with beavers. Our review proposes a low conflict strategy for rewilding with beavers that includes changes from a policy of conflict avoidance to a proactive policy to support practices that apply the tools of social-ecological systems science to the body of knowledge about the interactions between beavers and their environment.